2009
DOI: 10.1093/cercor/bhp246
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Expression of the Oligodendrocyte Myelin Glycoprotein in the Mouse Telencephalon

Abstract: The oligodendrocyte myelin glycoprotein is a glycosylphosphatidylinositol-anchored protein expressed by neurons and oligodendrocytes in the central nervous system. Attempts have been made to identify the functions of the myelin-associated inhibitory proteins (MAIPs) after axonal lesion or in neurodegeneration. However, the developmental roles of some of these proteins and their receptors remain elusive. Recent studies indicate that NgR1 and the recently discovered receptor PirB restrict cortical synaptic plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 76 publications
3
29
0
Order By: Relevance
“…Previous reports have shown similar results on the effect of age on Nogo-A level. For example, immunoblotting analyses have shown to decrease in expression of Nogo-A protein in developing telencephalon from embryo on day 16 to adult stages (Gil et al 2010). Similar finding is also reported by Mingorance et al (2004) where they have shown decrease in expression of Nogo-A from the day of birth (postnatal day 0) to adult stage in developing hippocampus.…”
Section: Resultssupporting
confidence: 83%
“…Previous reports have shown similar results on the effect of age on Nogo-A level. For example, immunoblotting analyses have shown to decrease in expression of Nogo-A protein in developing telencephalon from embryo on day 16 to adult stages (Gil et al 2010). Similar finding is also reported by Mingorance et al (2004) where they have shown decrease in expression of Nogo-A from the day of birth (postnatal day 0) to adult stage in developing hippocampus.…”
Section: Resultssupporting
confidence: 83%
“…The literature reveals that MAIs are not only expressed on the surfaces of axons but are also expressed in the synapses, which suggests that MAIs might participate in synaptic plasticity and stability [21] because receptors for Nogo-A, OMgp, NgR, and PirB are also expressed in the synapses. Indeed PirB expression was firstly detected close to the presynaptic membrane of neurons, which indicates that PirB localizes in or close to the synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Its role in developmental axon sprouting is still poorly understood [18]. Interestingly, OMgp is involved in the regulation of synaptic plasticity and activity-dependent synaptic strength [19], and it may influence axonal target specification during the development of thalamocortical projections [20]. In three independent studies, genetically deleting OMgp did not promote CST axon regeneration [9••,10••,21].…”
Section: Multiple Ligands and Multiple Receptors Involved In Axon mentioning
confidence: 99%